2021
DOI: 10.1007/s10948-021-05853-7
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Determination of the Orientation of Tilted Magnetic Anisotropy by Using Angle-Resolved Hall Effect Signals

Abstract: The orientation of the tilted magnetic anisotropy has crucial importance in many spintronic devices. However, it is very challenging to determine it especially in very small structures produced by lithography. Here, we propose a new experimental method to directly and accurately measure both the polar and azimuthal angles of a tilted magnetic anisotropy. By using the proposed experimental method, we have successfully determined the out-of-plane and in-plane angles of the tilted magnetic anisotropy in a micro-s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…Since then, several other ways of achieving a film with tilted magnetization have been considered, such as ferromagnetic coupling of a tilted top Co layer with an in-plane magnetized bottom Co layer [38]. Much attention has been paid in particular to L1 0 FePt and CoPt films [32,39], which can be deposited on the substrate in such a way that the unique tetragonal axis is strongly deviated from the plane of the film, as in the case of the growth of the FePt films with a (111) surface [33,34,40,41]. The L1 0 FePt (111) films in the aforementioned experiments have a thickness of 20 to 60 nm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, several other ways of achieving a film with tilted magnetization have been considered, such as ferromagnetic coupling of a tilted top Co layer with an in-plane magnetized bottom Co layer [38]. Much attention has been paid in particular to L1 0 FePt and CoPt films [32,39], which can be deposited on the substrate in such a way that the unique tetragonal axis is strongly deviated from the plane of the film, as in the case of the growth of the FePt films with a (111) surface [33,34,40,41]. The L1 0 FePt (111) films in the aforementioned experiments have a thickness of 20 to 60 nm.…”
Section: Introductionmentioning
confidence: 99%
“…FePt (111) films were also used in experimental pseudo spin valves [40], indicating a noticeable magnetoresistance, followed by a theoretical analysis of a spin valve with conical magnetization [43]. To directly measure angles of tilted magnetic anisotropy, Pişkin et al proposed a new experimental method using anomalous and planar Hall effects together and called it angleresolved Hall effect signals (ARHES) [39].…”
Section: Introductionmentioning
confidence: 99%
“…There exist other works that focus on non-contact anisotropy measurement, and are therefore more suitable for in-line process measurement. The dynamic response of the magnetic layers can be measured by using eddy current sensors [9,10], magnetic sensors [11], and ferromagnetic resonance (FMR) [6]. Doirat et al [9] observed the magnetic response of anisotropic metal fiber material by using a ferrite core eddy current sensor together with an impedance analyzer.…”
Section: Introductionmentioning
confidence: 99%